Lanthanum content and effects on growth, gas exchanges, and chlorophyll index in maize plants (Acta Scientiarum. Biological Sciences, 2018)
Rare earth elements, such as lanthanum (La), have been applied to agriculture via fertilizers, aiming to increase the productivity and crop quality, such results observed mainly in China. However, the knowledge about the effect of La on maize growth, as well as for other species, despite the growing interest it is still limited. The aim of this study was to evaluate the effects of La on maize growth, La content, photosynthetic rate and chlorophyll content in maize plants in response to La treatment (0, 25, 50, 100, 150, 300 and 600 Î¼M) in nutrient solution for three weeks. The plants were placed in geminated pots using a split-root technique. One of the pots in the geminated set was filled with a complete nutrient solution without La, while another was filled with a nutrient solution without phosphorus but containing different concentrations of La. It was verified that roots of maize plants can accumulate approximately sixty percent more La than shoots. Moreover, low La concentrations stimulated an increase in chlorophyll index, resulting in a slight increase in shoot biomass. At higher levels, La didn’t reduce growth but caused a decrease in both photosynthetic rate and chlorophyll index.